Analisa Pengaruh Variasi Komposisi Bahan Limbah dari Serat Kelapa Muda, Batang Pisang dan Kertas Bekas terhadap Kekuatan Bending Sebagai Papan Komposit - Enda Apriani (Proklamasi 45 University, 2017)
The composite is a combination of two or more materials to produce a new material with unique properties compared to the nature of the base material prior to mixing and surface bonding occurs between each constituent material. The purpose of this research is to know the influence of waste material composition from plant fiber, that is young coconut fiber, banana stem, and calendar waste paper to bending strength on composite board by using Epoxy resin wood type. The process of printing the composite board is done in the Laboratory of Integrated Mechanical Engineering University Proklamasi 45 Yogyakarta. The three raw materials that have been crushed and dried, mixed with the breaking time of each 5